Pengembangan Kemampuan Berpikir Matematis untuk Penguatan Disposisi Matematis Melalui Kolaborasi antara Siswa dan Guru - Tupulu, Nasri; Jamiah, Yulis; Rustam, Rustam; Fitriawan, Dona (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The purpose of this study was to determine the ability to think mathematically to strengthen mathematical dispositions through collaboration between students and teachers. Qualitative type research with R&D development research design. the data comes from 20 class XA students at Maniamas Ngabang High School in the matrix material for the 2021/2022 school year. The research results obtained that: 1) there are several steps of mathematical thinking ability to strengthen mathematical disposition through collaboration between students and teachers which can be seen during the process of learning activities and when solving matrix questions where students have fulfilled all four indicators of mathematical thinking ability seen from learning activities in The 2nd RPP namely deepening, guessing, generalizing, and convincing; 2) the ability to think mathematically to strengthen mathematical dispositions through collaboration between students and teachers is in accordance with the visible results of students' mathematical thinking abilities being met where students solve problems well and have indicators of ability to think mathematically and have an attitude of confidence, persistence, tenacity, in doing all math assignments and have a high curiosity in mathematics.